Effects of magnesium biotinate supplementation on serum insulin, glucose and lipid parameters along with liver protein levels of lipid metabolism in rats - Şahin, Kazım; Orhan, Cemal; Küçük, Ömersman; Erten, Fusun; Tuzcu, Mehmet; Şahin, Nurhan; Komorowski, James Richard (Jle, 2021)
The objective of this study was to investigate the effects of a novel form of biotin (magnesium biotinate) on serum glucose, lipid profile, and hepatic lipid metabolism-related protein levels in rats. Forty-two rats were divided into six groups and fed a standard diet-based egg white powdered diet supplemented with either d-biotin at 0.01, 1, or 100 mg/kg BW or magnesium biotinate at 0.01, 1, or 100 mg/kg BW for 35 days. Neither form of biotin influenced (p > 0.05) serum glucose or insulin concentrations. Serum total cholesterol and triglyceride decreased with biotin from both sources (p < 0.05). Concentrations were lower with magnesium biotinate when comparing the 1 mg/kg dose (p < 0.05). Serum, liver, and brain biotin and liver cyclic guanosine monophosphate (cGMP) concentrations were greater when rats were treated with magnesium biotinate versus d-biotin, particularly when comparing the 1 and 100 mg/kg dose groups (p < 0.05). Both biotin forms decreased the liver SREBP-1c and FAS and increased AMPK-alpha 1, ACC-1, ACC-2, PCC, and MCC levels (p < 0.05). The magnitudes of responses were more emphasized with magnesium biotinate. Magnesium biotinate, compared with a commercial d-biotin, is more effective in reducing serum lipid concentrations and regulating protein levels of lipid metabolism-related biomarkers.
Keywords: D-biotin; magnesium biotinate; glucose; insulin; lipid parameters